2018
DOI: 10.1136/flgastro-2018-101028
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic day case antireflux radiofrequency (Stretta) therapy improves quality of life and reduce proton pump inhibitor (PPI) dependency in patients with gastro-oesophageal reflux disease: a prospective study from a UK tertiary centre

Abstract: BackgroundEndoscopic antireflux radiofrequency treatment (Stretta) offers a therapeutic alternative for patients suffering from refractory gastro-oesophageal reflux disease (GORD). Current evidence suggests that the treatment may improve symptoms of GORD and decrease requirement for proton pump inhibitor (PPI) therapy.MethodsProspective assessment of patients undergoing Stretta, between October 2014 and February 2016, in a UK tertiary referral centre was carried. All patients were assessed for suitability usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Nissen's fundoplication is performed to treat GERD and HH. 7,8 GERD is a common illness that impacts large numbers of the population in the modern era. A minority of patients Minimal Invasive Surgery for GERD and HH Harvitkar, Joshi with GERD have a constantly weak low pressure LES (less than 6 mm Hg), which allows reflux every time the pressure in the stomach exceeds LES pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nissen's fundoplication is performed to treat GERD and HH. 7,8 GERD is a common illness that impacts large numbers of the population in the modern era. A minority of patients Minimal Invasive Surgery for GERD and HH Harvitkar, Joshi with GERD have a constantly weak low pressure LES (less than 6 mm Hg), which allows reflux every time the pressure in the stomach exceeds LES pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Nissen's fundoplication is performed to treat GERD and HH. 7,8 GERD is a common illness that impacts large numbers of the population in the modern era. A minority of patients The diagnosis of GERD is typically made by corelating symptoms and objective test results.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for STRETTA in our center are in conformity with the NICE guideline according to which, if proton pump inhibitor (PPI) medication has failed to resolve the symptoms, endoscopic radiofrequency therapy may be used before or after the surgery. 3…”
Section: Methodsmentioning
confidence: 99%
“…Two multicenter, prospective, and observational studies assessed 55 and 138 patients undergoing the Stretta procedure, respectively. The first study showed that the average GERD-Health Related Quality of Life (GERD-HRQL) score decreased to 15.2 post-operatively from 46.2 preoperatively after 771-day follow-up [ 42 ]. The second study with a 5-year follow-up evaluated the improvement in GERD-associated symptoms and found that the severity of heartburn, thoracalgia, and asthma was obviously relieved after the Stretta procedure, and 42.8% of patients completely ceased to take PPIs.…”
Section: Introductionmentioning
confidence: 99%